Anime and its roots in early Japanese monster art - Papp, Zilia (Global Oriental, 2010)
Japanese anime plays a major role in modern popular visual culture and aesthetics. This study puts today's anime in historical context by tracking the visual links between Edo- and Meiji- period painters and the post-war period animation and manga series Gegegeno Kitaro by Mizuki Shigeru.